Phytochemical Screening And Antibacterial Activity Test Of Ethanol Extract Of Jengkol Leaves (Archidendron Pauciflorum Benth.) I.C. Nielsen Against Staphylococcus Epidermidis And Propionibacterium Acnes - Munandar Nasution, Haris; Yuniarti, Rafita; Rani, Zulmai; Nursyafira, Arini (International Journal of Science, Technology & Management, 2022)
Skin disease was a disease that attacked the surface of the body, and was caused by various agents, one was bacteria. One of the plants that had antibacterial activity was jengkol leaf (Archidendron pauciflorum Benth.) I.C. Nielsen because it contained compounds that had antibacterial properties that had previously been studied by other researchers against Staphylococcus aureus and Escherichia coli bacteria. So that researcher was interested in researching on the antibacterial activity of jengkol leaves (Archidendron pauciflorum Benth.) I.C. Nielsen against Staphylococcus epidermidis and Propionibacterium acnes. Fresh Jengkol leaves were processed into simplicia and extracted using 96% ethanol. Phytochemical screening was carried out on simplicia powder and extracts of jengkol leaves. Ethanol extract jengkol leaves was made in several concentrations, namely 20%, 25%, and 30%, positive control using Tetracycline HCl, and negative control using 1% DMSO. There were several tests carried out on jengkol leaves in addition to phytochemical screening, namely examination of simplicia characteristic including macroscopic examination, microscopic examination, examination of water content, examination of water-soluble extract levels, examination of ethanol-soluble extracts, examination of total ash content, and also an examination of acid-insoluble ash levels and antibacterial activity test of jengkol leaves. The results of phytochemical screening showed that the compound of jengkol leaves (Archidendron pauciflorum Benth.) I.C. Nielsen contained a class of secondary metabolites of alkaloids, flavonoids, tannins, saponins, steroids/triterpenoids, and glycosides. And for the results of the antibacterial activity research also showed that jengkol leaves could be used as antibacterial because it has a strong inhibitory power at a concentration of 20% and the strongest at a concentration of 30% against Staphylococcus epidermidis, namely 15.06 mm and 17.83 mm, while in diameter of growth inhibition zone Propionibacterium acnes was 15.86 mm and 18.1 mm.